Relacja pomiędzy teorią umysłu a więzami społecznymi. Co możemy z nią zrobić? - Eden, Chen (Studia Edukacyjne, 2020)
The aim of this article is to examine whether the attitude towards the deficiency of people with the Autistic Spectrum Disorder relies on the Theory of Mind concept and the symbolic interaction approach. Autism is a deficiency hampering the ability to receive messages from others and develop appropriate mutual relations. The deficiencies are apparent in three areas of development – social functioning, communication and behaviour. The study population are high functioning people with autism – ASD. TOM is a concept of consciousness, the ability to understand and interpret human behaviour in interactions and social contexts, including the ability to identify mental states such as: emotions, thoughts, intentions and desires of the individual and those around him. There are three components within this interaction: cognitive (thoughts, beliefs), emotional (exhibiting and understanding emotions, empathy), and the behavioural component (the actual interaction). Symbolic interactionism is a sociological paradigm claiming that social reality is based on the interactions between individuals in society, based on symbols and interpretations. When we examine the interaction of people with ASD, in order to understand their social thinking, emotions and behaviours we want to have a framework focusing on the interaction within a group. One of important and meaningful groups is the peer group, which has an important general and specific role in youth and young adults. The peer group has a significant role in integrating personal identity, establishing a different status within the family, and acquiring greater autonomy in the world outside the family. Work within the peer group enables familiarization with the deficiency and different parts of the “self”, thus con-structing a solid identity and closer relations with the environment. Group work will include aspects such as projection, giving and receiving feedback, learning about emotional mirroring, and defending oneself.